Time-Controlled SPAD Receivers in Optical Wireless Communication System - Junzhi Liu; Wei Jiang; Shiva Kumar; M. Jamal Deen (IEEE Photonics Journal, 2023)
Single-photon avalanche diodes (SPADs) capable of single photon detection are promising optical sensors for use as receivers in optical wireless communication (OWC) systems. In SPAD-based receivers, the intersymbol interference (ISI) effect caused by dead time is an important drawback that limits performance. In this paper, we propose two novel SPAD operation modes to reduce the ISI effect in SPAD-based OWC. To validate the feasibility of these two modes, we designed a free-running SPAD front-end circuit with post-layout transient simulation results and some measurements to show its function and performance. This SPAD circuit is improved by a novel mixed passive-active quench and reset front-end circuit that achieves a very short dead time. Based on the traditional free-running mode, we design the clock-driven mode and time-gated mode to reduce the ISI effect through time-controlled operating signals. To accurately evaluate these three modes, we develop a new simulation system to assess the ISI effect in On-Off Keying (OOK) modulated communication. The simulation results demonstrate that the clock-driven mode and time-gated mode receivers can improve the bit error rate (BER) performance in low data rate communication and high data rate high optical power communication, respectively. Moreover, compared to the free-running mode, the two proposed time-controlled modes achieve higher data rate communication and better noise tolerance ability in SPAD-based OWC.